Evaluation Performance of Pneumatic Dryer for Cassava Starch - Suherman Suherman; Nur Hidayati (Dept. of Chemical Engineering, Diponegoro University, 2018)
In small and medium industries, cassava starch is dried using conventional method by drying it directly under the sun. However, the main drawback of conventional method is low drying rate. Therefore, in this study, cassava starch with a water content of 40% (wet basis) was dried using a pneumatic dryer to a moisture content below 13% (wet basis). The aim of this research is to analyze the influence of drying air temperature, drying air flow rate and rate of feeding in relation to drying rate and energy analysis. Energy analysis was performed to determine the performance of pneumatic dryer. The energy analysis itself is done in the form of energy utilization and energy efficiency. The energy analysis shows that the increase of dryer temperature from 60 to 100oC will increase the utilization of energy from 0.34 to 0.76 J/s, while the energy efficiencies ranged between 30-40%. Proximate analysis shows that the dried cassava starch has an ash content of 0,24, grain fiber of 0,12, and degree of whiteness of 98%, which fulfills the SNI standard of cassava starch.Keywords: cassava starch; energy analysis; pneumatic dryer